Crossroads between Bacterial and Mammalian Glycosyltransferases - Brockhausen, Inka (Frontiers in Immunology, 2014)
Bacterial glycosyltransferases often synthesize the same glycan linkages as mammalian glycosyltransferases, yet they usually have very little sequence identity. Nevertheless, the properties, folding, substrate specificities and catalytic mechanisms of these enzyme proteins may have significant similarity. Thus bacterial glycosyltransferases can be utilized for the enzymatic synthesis of both bacterial and mammalian types of complex glycan structures. A comparison is made here between mammalian and bacterial enzymes that synthesize epitopes found in mammalian glycoproteins, and those found in the O antigens of Gram negative bacteria. These epitopes include Thomsen-Friedenreich (TF or T) antigen, blood group O, A and B, type 1 and 2 chains, Lewis antigens, sialylated and fucosylated structures and polysialic acids. Many different approaches can be taken to investigate the substrate binding and catalytic mechanisms of glycosyltransferases, including crystal structure analyses, mutations, comparison of amino acid sequences, NMR and mass spectrometry. Knowledge of the protein structures and functions helps to design glycosyltransferases for specific glycan synthesis and to develop inhibitors. The goals are to develop new strategies to reduce bacterial virulence and to synthesize vaccines and other biologically active glycan structures.